Regulatory Capacity of Local Governments in Resolving Contemporary Environmental Disputes through Integrated Restorative Approaches and Civil Governance Mechanisms - Patria Adiguna; Arvy N. Osma; Moh. Mujibur Rohman (International Forum of Researchers and Lecturers, 2024)
This study explores the effectiveness of restorative and civil governance models in resolving environmental disputes at the local government level. As environmental conflicts become more complex and widespread, traditional legal approaches often fail to provide quick, sustainable solutions. Restorative governance models, which prioritize community involvement, collaboration, and the restoration of relationships, offer a promising alternative to adversarial legal proceedings. The research combines policy analysis and semi-structured interviews with local government officials, mediators, and community representatives to assess the implementation and outcomes of these models in real-world contexts. Findings indicate that restorative practices, when integrated with civil governance mechanisms, significantly reduce dispute resolution times (a 40% improvement) and enhance community satisfaction compared to traditional litigation processes. These models foster a more inclusive and cooperative environment, ensuring that all stakeholders, including local communities, are actively involved in decision-making processes. However, challenges such as legal framework rigidity, political pressures, and resource limitations still impede the widespread adoption of restorative practices. The study concludes with recommendations for integrating restorative approaches into local environmental policies, advocating for legal reforms and enhanced resource allocation to support these methods. Limitations of the study include its regional focus and the need for broader, longitudinal research to assess the scalability of restorative and civil governance models across different geographic contexts and environmental issues.